Teaching inclusive education: a contextual higher education analysis - Korkie, Yolande; Beyers, Christa; Swanepoel, Eben (Frontiers in Education, 2025)
While it is widely acknowledged that inclusive education policy is the suitable approach for addressing the diverse needs of South African learners, research in the pilot stages of Education White Paper 6 warned that the implementation of this policy would be complex. Studies have elucidated that there is a chasm between policy and theory on the one hand, and practice on the other hand; a gap between knowledge and the interactional expression thereof. Drawing on qualitative data collected from thirty-nine (39) pre-service teachers (students) and eight (8) lecturers, this paper articulates three themes. Student participants possessed some knowledge regarding aspects of inclusive education, but they lacked the practical demonstration and application thereof. Lecturer participants, on the other hand, felt pressured to cover module content in a limited time, greatly influencing their attitudes towards inclusive practices. The lecturer participants furthermore suggested that their own knowledge was insufficient to prepare future teachers adequately. This paper proposes that in-service training centered on contextual inclusive educational skillsets and knowledge for lecturers and teachers should be prioritized. Modules should be integrated inter-disciplinarily, based on inclusive education policy, to adequately prepare pre-service teachers to meet the needs of the diverse group of learners that they will teach.